Digitalisasi Demokrasi dalam Penerapan E-Voting Pada Pilkades di Kabupaten Bantaeng, Sulawesi Selatan - Muhammad Halwan; Muhadjir Darwin; Setiadi Setiadi; Nanang Indra Kurniawan (Pencerah, 2022)
This study aims to analyze the digitalization of democracy in the implementation of e-voting in Pilkades in Bantaeng Regency, South Sulawesi. This study is based on qualitative research by gathering data through observation, interviews and questionnaires. The results of this study indicate that, first, the implementation of e-voting policies as a political innovation is carried out by formulating policies, namely compiling regulation as the first step in the process of public policy innovation. Second, the process of implementing e-voting consist of several stages, namely the stages of the preparation, nomination, voting, final recapitulation and inauguration where the preparatory stage to the final recapitulation is not much different from the conventional Pilkades implementation (paper based). The difference lies more in the use of electronic systems. The form of using electronic application in voting through the direct electronic recording (DRE) system. Third, evaluation of the e-voting policy based on the five aspects evaluated related to the implementation of e-voting in village head elections, as a whole that the five aspects which include effectiveness, efficiency, fairness, adequacy and responsiveness can be stated that the process has been carried out properly in accordance with the indicators or standard e-voting implementation criteria in village head election. Furthermore, evaluation of fie aspects is also a concern for the government regarding improvement to the implementation of e-voting in village head election. With improvements in some of these aspects, it can be stated that the application of e-voting in village head election as a political innovation can be continued as part of the process of digitizing democracy.